Focal dermal hypoplasia (Goltz Syndrome): A cross-sectionalstudy from Eastern India - Sudip Kumar Ghosh; Abhijit Dutta; Sharmila Sarkar; Shanka Subhra Nag; Surajit Kumar Biswas; Prabhakar Mandal (Wolters Kluwer Medknow Publications, 2017)
Introduction: Focal dermal hypoplasia (Goltz syndrome), is an extremely rare genetic disorder characterized by distinct skin manifestations and a wide range of abnormalities involving the ocular, dental, skeletal, urinary, gastrointestinal, cardiovascular, and central nervous systems. The objective of the present series is to emphasize the different typical as well as unusual features of this rare syndrome. Methology: This cross-sectional observational study was performed over a period of 8 years in a tertiary care hospital of Eastern India. Consecutive patients with the clinical diagnosis of Goltz syndrome were studied. Results: A total of 8 patients with Goltz syndrome were evaluated. Out of them, one patient was a boy and the rest were girl. The age ranged from 3 days to 9 years. There was no family history. A characteristic Blaschkoid hypo- and hyper-pigmented skin lesions, congenital nodular fat herniation, and skin atrophy were present in all patients. Congenital cutaneous aplasia was present in 50% of the patients. Facial asymmetry and ear deformity (megalopinna and low-set ears) were seen in 37.5% and 12.5% of patients, respectively. Cutaneous telangiectasia was noticed in 37.5% of patients. Freckle- and lentigines-like pigmentation within the hypopigmented macules was found in 25% of patients. Raspberry-like papillomas around mouth were documented in 6 (75%) patients. Dysplastic nail changes with ridging were seen in 7 (87.5%) patients. Genital abnormality in the form of bilateral undescended testes and microphthalmia with aniridia were found in one patient each. Limb defects were present in all patients. Left-sided renal agenesis was found in one patient. The patient also had multiple cortical cysts of the right kidney. Limitations: Genetic testing could not be performed in the present series. Conclusions: Our case series showed a few unusual or extremely rare manifestations such as undescended testes, dermal sinus, kyphoscoliosis, aniridia, unilateral kidney agenesis, and renal cortical cysts among others.